2018
DOI: 10.3389/fmars.2018.00257
|View full text |Cite
|
Sign up to set email alerts
|

Boom and Bust: Life History, Environmental Noise, and the (un)Predictability of Jellyfish Blooms

Abstract: Jellyfish (pelagic Cnidarians and Ctenophores) form erratic and seemingly unpredictable blooms with often large, transient effects on ecosystem structure. To rapidly capitalize on favorable conditions, jellyfish can employ different life histories, which are either a life cycle with one annual sexual reproduction event and an overwintering benthic stage (metagenic life cycle), or continuous reproduction and a holoplanktonic life cycle. However, the links between life history, blooms, and environmental variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…During warm years such as El Niños, food webs tend to be more elongated with additional intermediate trophic levels compared to cool years, leading to less trophic efficiency in the system (Brodeur and Pearcy, 1992;Ruiz-Cooley et al, 2017). The increased densities of these gelatinous microcarnivorous predators such as Aequorea victoria may have depressed populations of grazing copepods, thus creating a trophic cascade typical of many jellyfish blooms (Schnedler-Meyer et al, 2018), leading to the high chlorophyll levels we observed in 2015. In contrast, pelagic tunicates such as pyrosomes feed on smaller particles including phytoplankton (Perissinotto et al, 2007, but see Pakhomov et al, 2019), which may have depressed chlorophyll a levels as seen in 2016.…”
Section: Discussionmentioning
confidence: 87%
“…During warm years such as El Niños, food webs tend to be more elongated with additional intermediate trophic levels compared to cool years, leading to less trophic efficiency in the system (Brodeur and Pearcy, 1992;Ruiz-Cooley et al, 2017). The increased densities of these gelatinous microcarnivorous predators such as Aequorea victoria may have depressed populations of grazing copepods, thus creating a trophic cascade typical of many jellyfish blooms (Schnedler-Meyer et al, 2018), leading to the high chlorophyll levels we observed in 2015. In contrast, pelagic tunicates such as pyrosomes feed on smaller particles including phytoplankton (Perissinotto et al, 2007, but see Pakhomov et al, 2019), which may have depressed chlorophyll a levels as seen in 2016.…”
Section: Discussionmentioning
confidence: 87%
“…Bordehore et al, ) to quantify and evaluate the development of jellyfish blooms from a food web perspective (cf. Schnedler‐Meyer, Kiørbøe, & Mariani, ). Although the temporal and spatial patterns of abundance in each life stage may vary according to jellyfish species (Lucas et al, ; Scorrano, Aglieri, Boero, Dawson, & Piraino, ) and even across populations of the same species (Dawson et al, ), our observations on the moon jellyfish are likely describing general trends.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the polyp stage of jellyfish is largely focussed on common species and almost exclusively lab-based, with the patterns observed being locale-and species-dependant. Modelling of jellyfish life cycles is still relatively new, with the focus of previous modelling studies also being locale-and species-dependant (Henschke et al, 2018;Schnedler-Meyer et al, 2018). Higher temperature within PlankTOM11 increases the growth rate, which translates into increased biomass if there is sufficient food, thus providing a representation of an increasing medusa population.…”
Section: Discussionmentioning
confidence: 99%